2016
DOI: 10.4038/sljss.v39i1.7400
|View full text |Cite
|
Sign up to set email alerts
|

Emotioncy: a post-linguistic approach toward vocabulary learning and retention

Abstract: Inspired by the Developmental Individual-difference Relationship-based (DIR) model of first language acquisition and Emotion-Based Language Instruction (EBLI) in bilingual education, the current study explores the function of emotioncy as an effective benchmark for vocabulary teaching. In particular, it attempts to empirically extend the earlier work on emotioncy, investigate learners' vocabulary development, and draw a link between learners' emotioncy and their diverse socio-economic backgrounds. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Additionally, the reviewed studies in English language teaching revealed that emotioncy has received more attention than the other five fields. The researched topics ranged from language skills (i.e., willingness to read, willingness to communicate, readability measurement, vocabulary retention) (see Pishghadam and Shayesteh, 2016 ; Shahian et al, 2017 ; Borsipour et al, 2019 ; Makiabadi, 2020 ) to life syllabus (Shakeebaee, 2020 ), emotionalization (Shakeebaee et al, 2017 ), teacher emotional labor and teacher burnout (Momenzadeh, 2020 ), test bias (Pishghadam et al, 2017a ), emo-sensory capital (Pishghadam et al, 2018a ) and Emotion-based language instruction (Pishghadam et al, 2013 ). There is abundant room for future studies on other areas of English language teaching, particularly other language skills, in light of emotioncy study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the reviewed studies in English language teaching revealed that emotioncy has received more attention than the other five fields. The researched topics ranged from language skills (i.e., willingness to read, willingness to communicate, readability measurement, vocabulary retention) (see Pishghadam and Shayesteh, 2016 ; Shahian et al, 2017 ; Borsipour et al, 2019 ; Makiabadi, 2020 ) to life syllabus (Shakeebaee, 2020 ), emotionalization (Shakeebaee et al, 2017 ), teacher emotional labor and teacher burnout (Momenzadeh, 2020 ), test bias (Pishghadam et al, 2017a ), emo-sensory capital (Pishghadam et al, 2018a ) and Emotion-based language instruction (Pishghadam et al, 2013 ). There is abundant room for future studies on other areas of English language teaching, particularly other language skills, in light of emotioncy study.…”
Section: Resultsmentioning
confidence: 99%
“…This shift could be both forward and backward along with the emotioncy continuum levels. For example, someone involved in a task might get exvolved or metavolved with time (Pishghadam and Shayesteh, 2016 ). Hence, human socialization processes and internal and external mandates could influence their emotioncy levels in one way or another.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rodriguez-Esteban and Rzhetsky (2008) showed the dominance of a sensedeprived style in biomedical texts by analyzing more than 250000 articles. Moreover, individuals` perspectives of reality and outlook on the future can be influenced by their emotions and sensory inputs from their surroundings (Pishghadam & Shayesteh, 2016). Existing senses are primarily responsible for their connections to themselves, other persons, and other organisms (Pishghadam & Shakeebaee, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Following Pishghadam et al (2021b) and Shayesteh et al (2020) , we elaborated on the meaning and features of the selected items in a session we called the instruction session. To control the weight of senses in giving the instructions, we relied on previous behavioral (e.g., Pishghadam and Abbasnejad, 2016 ; Pishghadam and Shayesteh, 2016 ; Pishghadam et al, 2018 ) and electrophysiological ( Shayesteh et al, 2020 ; Pishghadam et al, 2021a , b ) studies and used Pishghadam (2016) sensory-based model of emotioncy (emotion + frequency) which exclusively illustrates different combinations of senses. The model sets the ground for discriminating a blend of visual, auditory, and kinesthetic/tactile senses (coined as exvolvement) from a combination of auditory, visual, kinesthetic/tactile, olfactory, and gustatory modalities (coined as involvement).…”
Section: Introductionmentioning
confidence: 99%